Resonant step-down DC-DC converter based on GaN power integrated circuits and SiC diodes - Stala, Robert; Folmer, Szymon; Mondzik, Andrzej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
In the paper results of the operation and efficiency of a DC-DC resonant converter with a switched capacitor topology, equipped with GaN transistors and SiC diodes are presented. Investigated problems are related to the optimization of the DC-DC power electronic converter in order to achieve miniaturization, a simplified design, and high efficiency. The proposed system operates at a high frequency with low switching losses. The proposed design helps to achieve uniform heating of the transistors and diodes, as demonstrated by the results of the thermal imaging measurements. The GaN transistors are integrated into one package with dedicated gate drivers and used to simplify the circuitry of drivers and increase the power density factor of the proposed device. In the high-frequency design presented in the paper, the converter is implemented without electrolytic capacitors. The results included in the paper contain waveforms recorded in the power circuit at ZVS operation when switching on the transistors. It occurs when the system operates above the frequency of current oscillations in the resonant circuit of the switched capacitor. Efficiency characteristics and a voltage gain curve of the converter versus its output power are presented as well. The results of efficiency and quality of waveforms are important because they facilitate characterizing the tested system for implementation using WBG devices. The use of integrated GaN modules to minimize elements in the physical system is also unique to this model and it allows for very short dead-time use, and operation in ZVS mode at low reverse-conduction losses.